"I can't evn get why she would make me rite in her class:" Using think-alouds in middle school math for "at-risk" students. Issue 4 (7th August 2016) - Bernadowski, Carianne
Abstract: A qualitative case study design was used to explore the use of the think-aloud reading comprehension strategy in the implementation of math journals. The goal of the study was to determine if a teacher's direct instruction in the implementation of think-alouds improved "at risk" eighth-graders' abilities to answer word problems more effectively over the course of eight weeks. Results indicate that students improved in their abilities to articulate their answers in written form, use and apply the writing process in math, and improve their dispositions and self-efficacy toward writing.